Type V Takayasu arteritis with multivessel involvement: diagnostic challenges and imaging insights in a young female: A case report - Zahin Shahriar, MBBS; Deluwar Hussen, MBBS; Shaimul Reza, MBBS; Afia Zahin, MBBS; Anusree Das, MBBS (Radiology Case Reports)
Takayasu arteritis (TA) is a rare vasculitis primarily affecting large arteries, leading to stenosis, occlusion, and aneurysm formation. Early diagnosis is difficult due to nonspecific symptoms. We present a case of a 30-year-old hypertensive female with progressive weakness, pain, and numbness in her limbs. Physical examination revealed absent pulses in the left upper limb and lower limbs, and elevated blood pressure. Imaging showed a ''macaroni sign'' on carotid ultrasound and significant vascular involvement, including aneurysmal dilation of the ascending aorta and narrowing of the carotid and renal arteries on CT angiography. The patient was managed medically due to financial constraints. Takayasu arteritis often progresses to vascular complications, requiring imaging for accurate diagnosis and assessment of vascular damage. Early detection and appropriate treatment are essential to prevent irreversible damage.